2012
DOI: 10.1038/ncomms1785
|View full text |Cite
|
Sign up to set email alerts
|

Strong-coupling d-wave superconductivity in PuCoGa5 probed by point-contact spectroscopy

Abstract: Superconductivity is due to an attractive interaction between electrons that, below a critical temperature, drives them to form Cooper pairs and to condense into a ground state separated by an energy gap from the unpaired states. In the simplest cases, the pairing is mediated by lattice vibrations and the wavefunction of the pairs is isotropic. Less conventional pairing mechanisms can favour more exotic symmetries of the Cooper pairs. Here, we report on point-contact spectroscopy measurements in PuCoGa5, a mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 54 publications
4
51
1
2
Order By: Relevance
“…The results indicate an occupation number of the Pu 5f shell very close to 5, corresponding to a stable Pu 3+ configuration, in contrast to δ-Pu and PuCoGa 5 for which an intermediate valence configuration has been suggested. 22 The high temperature anomalies that are always present in the parent RFeAsO compounds are not observed in PuFeAsO, and so we would suggest that, similar to NpFeAsO, spin density wave condensation and structural phase transition are not present in PuFeAsO. Continuing the trend from Np to Pu and on to Am, one might imagine that the increased degree of localization of the Am 5f electrons might be more compatible with a magnetic structure on the iron independent of that on the f electron ion, such that the SDW and related structural transition might be present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate an occupation number of the Pu 5f shell very close to 5, corresponding to a stable Pu 3+ configuration, in contrast to δ-Pu and PuCoGa 5 for which an intermediate valence configuration has been suggested. 22 The high temperature anomalies that are always present in the parent RFeAsO compounds are not observed in PuFeAsO, and so we would suggest that, similar to NpFeAsO, spin density wave condensation and structural phase transition are not present in PuFeAsO. Continuing the trend from Np to Pu and on to Am, one might imagine that the increased degree of localization of the Am 5f electrons might be more compatible with a magnetic structure on the iron independent of that on the f electron ion, such that the SDW and related structural transition might be present.…”
Section: Discussionmentioning
confidence: 99%
“…A similar calculation performed for the PuCoGa 5 superconductor yields n f = 5.30 and n f + n bath = 14, corresponding to a singlet ground state for the composite cluster. 22 This suggests that the f electrons in PuFeAsO are less hybridized with the conduction band than in PuCoGa 5 and are close to a static integer valence.…”
Section: Mj Kmentioning
confidence: 99%
“…Further arguments in favor of SFs-controlled SC were provided by NMR studies [2], revealing a nodal-gap function separating the condensate from the unpaired states. Subsequent point-contact spectroscopy measurements confirmed that the wavefunction of the paired electrons has an unconventional d-wave symmetry [3]. However, the SF conjecture was questioned [4,5] after polarized neutron diffraction failed to observe a local magnetic moment in the normal state of PuCoGa 5 [6], pointing to an extrinsic origin of the reported temperature dependent χ m .…”
mentioning
confidence: 99%
“…Fifteen years after its discovery [1] our understanding of much of this material remains at best confused [2][3][4][5][6][7][8]. We do know from NMR [2] and point-contact spectroscopy [6] measurements that the superconducting state has d-wave symmetry. Magnetic form-factor measurements with polarized neutron diffraction [5] have shown that the ground state is not the conventional 5f…”
Section: Introductionmentioning
confidence: 99%